Cytotaxonomical remarks on Loncomelos visianicum (Hyacinthaceae), a poorly known species endemic to Croatia - Bogdanović, Sandro; Brullo, Salvatore; Ljubičić, Ivica; Rat, Milica; Salmeri, Cristina (Phytotaxa, 2020)
Loncomelos visianicum, a rare and poorly known geophyte of the Croatian flora, was described from the remote and uninhabited Adriatic island of Palagruža as Ornithogalum visianicum, and it has not been collected again for over a century. Basing on living materials, recently rediscovered in the locus classicus, it was possible to carry out a careful investigation regarding the morphology, karyology, leaf anatomy, and ecology of this very peculiar species. It is triploid, showing 2n = 42 + 0–5B chromosomes, taxonomically quite isolated, showing some morphological relationships with L. narbonense and L. creticum. Currently, L. visianicum is represented by a low number of individuals growing in rocky places within the xerophilous maquis. In addition to a detailed description, a new iconography, conservation status and identification key for Croatian taxa of the genus Loncomelos are also provided.